The Effect of Practical Learning on Creative Thinking Skills of High School Students on Acid-Base - Sayid Z. S. Alwi; Suherman Suherman (Jurnal Akademika Kimia, 2020)
This study aims to determine the effect of practical learning on the creative thinking skills of class XI students on acid-base material at SMAN 7 Palu. This type of research was a quasi-experimental research with equivalent control group design. Sampling in this study was a purposive random sampling technique. The sample consisted of two classes students in XI MIA 2 as the experimental class (n = 24) and students in class XI MIA 4 as the control class (n = 24). Data from students' creative thinking using the one-party hypothesis testing, the right side were in this study used the statistics application and obtained sig. (2-tailed) 0,000 data based on this decision, the hypothesis is accepted if the sig (2-tailed) value is smaller than 0.05 so that it can be concluded that there is a positive effect using practical learning on the creative thinking ability of class XI students on acid-base material at SMAN 7 Palu.